Relación en la protección hidrológica y la cobertura vegetal de la secuencia hidrográfica del río carrizal - Lucas Loor, Karen Leonela (2016)
The relationship between the hydrological protection and the vegetation cover of the Carrizal hydrographic sub-basin was determined by calculating the Hydrological Protection Index (IPH). To do this, data obtained from field visits are used to 28 reference points processed through computer programs such as Excel and Geographic Information Systems. The number of reference points determined from the 15 land uses, specified for the study area according to the National Information System (SNI), known to the various authors that a larger area by coverage, number of Points of the mayor. In order to calculate the HPI, the following variables were analyzed: structure, density, interception of precipitation, presence of mulch, special characteristics, type of vegetation and degree of intervention with scale of 1 to 3 in transects radiated of 50 m, 5m. According to the calculation, the sub-basin has an area of 5945.55 ha., Where the vegetation cover with high hydrological stability is 70% tropical arboriculture / 30% intervened forest, with an HPI of 0.873. Cultivated pasture and shrubby vegetation with IPH 0.381 is equivalent to low, which is the most worrying index because it does not favor water retention, as opposed to runoff and soil erosion. In general, the hydrological protection of the Carrizal sub-basin is medium (IPH 0.590), which means that mitigation measures are needed, such as planting of tree species with great frondiness.